2007
DOI: 10.1128/aac.01109-06
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Stability of Integrons in Clinical Isolates of Shigella spp. of Worldwide Origin

Abstract: Over a 12-year period, 68 Shigella strains (31 S. sonnei, 30 S. flexneri, 4 S. dysenteriae, and 3 S. boydii strains) were collected in a French University Hospital from the stools of patients who generally had a recent history of travel to various parts of the world (91%), particularly Africa (67%). These strains were often resistant (streptomycin, spectinomycin, trimethoprim, tetracycline, and sulfonamides, 66 to 84%; ampicillin and chloramphenicol, 34 to 38%; nalidixic acid, 4%) and even multiresistant (87%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
8
25
1
3
Order By: Relevance
“…Here we found that 87.5% of 32 Shigella strains isolated in Senegal contained at least one integron. This marked dissemination of integrons among Shigella spp is partly linked to the propensity of this genus to acquire plasmids, as multidrug resistance integrons are usually plasmidborne [18]. In this study, class 1 integrons were the most prevalent, in keeping with the results of other studies of African Shigella isolates [18].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Here we found that 87.5% of 32 Shigella strains isolated in Senegal contained at least one integron. This marked dissemination of integrons among Shigella spp is partly linked to the propensity of this genus to acquire plasmids, as multidrug resistance integrons are usually plasmidborne [18]. In this study, class 1 integrons were the most prevalent, in keeping with the results of other studies of African Shigella isolates [18].…”
Section: Discussionsupporting
confidence: 77%
“…Dubois et al described Shigella strains containing a class 1 integron in which these two cassettes were followed by the insertion sequence IS1. Successful amplification with primers AadA3 and is1b (5'-GTGAACGCACTATGGCGACGC TG-3'), located within IS1 [17], confirmed that the genetic environment was the same as that described by Dubois et al [18].…”
Section: Cassette Arrayssupporting
confidence: 55%
See 1 more Smart Citation
“…Multi-resistance was verified in 87 % of the isolates, and a total of 13 antibiotic resistance patterns were identified (13). …”
Section: Human Fecal Samplesmentioning
confidence: 99%
“…About 10 % of bacterial genomes that have been partially or completely sequenced harbor this genetic element (Boucher et al 2007). The spread of antimicrobial-resistance genes by integrons was extensively investigated primarily in clinical settings (Grape et al 2003;Pan et al 2006;Dubois et al 2007). Nowadays, increased interest in their environmental role is observed (Elsaied et al 2007;Gillings et al 2009;Elsaied et al 2011) and also reviewed by Stalder et al (2012).…”
Section: Introductionmentioning
confidence: 99%